PUBLIC SMOKING (Tufts Archival Research Center, 2007)
Report on first quarter of 1986 for issues of public smoking, excise taxes, advertising restrictions, accidental fire, media relations, coalitions, and other activities. Includes events, results, and negatives for each issue, including legislation, media coverage, and activities of other organizations.